Early specialization versus sport diversification in youth athlete-article review - Dugas, P. (Research & Investigations in Sports Medicine, 2017)
Sport specialization is an increasingly dangerous epidemic that is having a negative effect on amateur athletes and the sports they play. The idea of participating in sports is to develop well-round and diverse youth by promoting self-esteem, leadership, and relationship building with teammates as well as developing athletic abilities to be successful in a particular sport. Sport specialization seems to have stemmed from an increase in participation and rise in competitive nature of youth sport. Competition in youth sport helps to build character and teaches how to deal with adverse situations. However, the push to win by adults has led to an increased number of young athletes playing a particular sport year round in a competitive environment. Sport specialization is defined as specific year round training in a specific sport with the exclusion of all other sport activities [1]. The reason behind this seems to be the allure of college scholarships and large professional contracts. The reality is only a small percentage of high school athletes are able to compete at the collegiate level and an even small number continue professionally.